The impact of I-Pulih model toward Methamphetamine clients recovery in Puspen Tampin, Melaka, Malaysia - Audi Azizul, Muhammad Dhamir; Wan Jaafar, Wan Munira; Mohd Khir, Azlina; Amin, Samir Muhazzab (Human Resource Management Academic Research Society, 2022)
The i-Pulih model is one of the interventions introduced to the individuals with drug addiction problems in 2020 that provides treatment and rehabilitation programs including biological, psychological, spiritual and social component. This study aims to identify the impact of i-Pulih model toward methamphetamine client’s recovery that still regarded as a new venture in Malaysia. Therefore, it is very important for researchers to identify the impact of the i-Pulih model on methamphetamine addicts in Malaysia as methamphetamine clients dominate rehabilitation centers in Malaysia. This study offered a multiple recovery programme in the i-Pulih model and the healing environment of rehabilitation provides the support required for a successful recovery. Individualized treatment plans are included in rehab to assist patients in identifying and overcoming the underlying issues that led to their addiction. While the primary goal of a rehab facility is to help patients overcome addiction, those who attend addiction treatment will learn the skills required to live a productive, healthy, and happy life. This study uses interpretive phenomenology approach, in-depth interviews as a means of gathering information that will involve seven methamphetamine addicts from Pusat Pemulihan Penagihan Narkotik (PUSPEN) Tampin, Melaka. Purposive sampling was employed to find individual who have been through similar experiences so that cohesive information can be gathered. Researchers emphasised that informant was entirely voluntary and would be conducted in a face-to-face in-depth interview. Thematic analysis was used to analyse interview transcripts in NVivo Version 12. The findings showed that there was an impact of the i-Pulih model among clients in the dimension of self-efficacy and social interaction. The dimension of self-efficacy is demonstrating in term of self-alternative and self-regulation to facing recovery challenge. Meanwhile in social interaction, there was a reduction of anti-social behaviour, being socially selective, and confidence to socialize. Researchers suggested future research must provide a more in-depth analysis on the effectiveness of i-Pulih model in term of self-efficacy and social interactions during aftercare treatment. Expectantly, the effectiveness of i-Pulih model stay relevant as a current intervention in the synthetic drug abuse in line with the major focus of 2030 Agenda for Sustainable Development vision.